"¿Qué te parece Cliterio? ¿Quieres todavía ser soldado?": Diego Núñez Alba's Diálogos de la vida del soldado (1552) and soldiering in early modern Spain. (2nd October 2018) - Sherer, Idan
ABSTRACT: Diálogos de la vida del soldado (1552) by the Spanish veteran Diego Núñez Alba seems to be unjustifiably neglected in scholarship, especially when considering the overall interest in memoirs and autobiographies by other early modern Spanish soldiers. This neglect is peculiar considering the fact that the Diálogos are not only an instructive example of the writing of life stories in early modern Europe and the literary conventions that influenced it, but also an extraordinary source of information on the motivations of early modern soldiers to write their life stories. The aim of this paper is to demonstrate the frustration and hopelessness that often drove veterans of the Spanish tercios to attempt to address powerful political and military figures for financial and personal assistance and patronage by harnessing and employing established humanistic literary methods and conventions.